Analyzing Nursing Leadership at an Academic Historical Event: A Descriptive Study Based on Social Networks - Pilar Marqués-Sánchez; Greta Cummings; María Cristina Martínez-Fernández; María Lara Martínez-Gimeno; María López; Néstor Serrano-Fuentes (Elsevier, 2020)
Purpose: To analyze the leadership network structure among nursing leaders in Spain identified through the Grupo40Enfermeras y Universidad event. Methods: A descriptive cross-sectional study using social network analysis was used. Study sample consisted of 210 individuals, of whom 119 received nominations as referents. Structural analysis of the network was conducted using centrality and cohesion. Results: A network structure was generated in which different leadership strategies were identified through InDegree, Eigenvector, and Betweenness Centrality. Five leaders were identified as bridges to other individuals using Betweenness. The whole network presented little cohesion although two highly cohesive cores were detected by K-core measurements. Conclusion: A strategy is needed to support nursing leaders with high degree of Betweenness to serve as bridges to connect other nursing leaders.